[Highway strip maps of Australia]. Strathmerton-Narrandera, 191 km., Newell Highway national route 39 - Royal Automobile Association of South Australia; Royal Automobile Club of Victoria ([Adelaide] : RAA, 1974)
Highway strip map describing places, country traversed, points of interest, road conditions, and safety hints for motorists.
Keywords: New South Wales -- Road maps; Victoria -- Road maps; Newell Highway (N.S.W.) -- Maps